2021
DOI: 10.15642/jpai.2021.9.1.83-102
|View full text |Cite
|
Sign up to set email alerts
|

Pesantren and the Economic Development in the Perspective of Maqashid Al-Shari’ah

Abstract: Modernization to deliver the process in diversifying the socio-economic role of pesantren is undeniable things. Consequently, pesantren must take immediate action if they want to maintain their role and function. In this context, this article wants to describe the widespread mandate of a pesantren in Jember, namely Pesantren Nurul Qornain (PNQ), those takes part –not only empowerment in the field of education- but also play role in the development of economic enterprises. This is then reviewed in the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As it developed, it became a center of economic activity, education, and even a pioneer of influential political power. Zawiyah then became a pesantren and Sufism can practically be preserved until now (Jazil et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As it developed, it became a center of economic activity, education, and even a pioneer of influential political power. Zawiyah then became a pesantren and Sufism can practically be preserved until now (Jazil et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, pesantren in general still have many roles only in the field of Islamic education (tafaqquh fiddin). Meanwhile, not much effort has been made in developing the economy and entrepreneurship (Jazil et al, 2021;Mustari & Rahman, 2012).…”
Section: The Potential Of Pesantren In Entrepreneurship Developmentmentioning
confidence: 99%
“…Pesantren has now undergone many changes. Although pesantren in general still play a role in the field of Islamic education (tafaqquh fiddin), not much effort has been made in developing the economy and entrepreneurship, but many pesantren have succeeded in carrying out their roles and functions as community empowerment and economic development (Dzikri, 2019;Haryono, 2022;Jazil, Fahmi, Prasetia, Faizin, & Sholihuddin, 2021;Pohl, 2006). The role of pesantren in economic development can strengthen three functions pesantren, namely education, preaching, and community empowerment (Kemenag, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These issues underscore the imperative of forging robust collaborations among the government, Islamic Boarding Schools, and stakeholders to bolster the quality of Islamic Boarding School education, teacher training, and infrastructure development (Faristina et Thirdly, the research identified challenges in implementing the policy, including a lack of understanding and coordination between the government and Islamic Boarding School, resource limitations, and the need for modernizing Islamic Boarding School management to adapt to contemporary developments. The research also highlights the hurdles encountered in policy implementation, encompassing issues of government-Islamic Boarding School coordination, resource constraints, and the imperative need for modernization to bring Islamic Boarding School management in line with contemporary developments (Anah, 2021(Anah, , 2022Awwaliyah, 2019;Bashori, 2017;Budiwiranto, 2019;Hasan, 2015;Jazil et al, 2021;Shofiyyah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%